Minimally Invasive Video-Assisted Thyroidectomy versus Conventional Thyroidectomy in Pediatric Patients - De Napoli, Luigi; Spinelli, Claudio; Ambrosini, Carlo Enrico; Tomisti, Luca; Giani, Carlotta; Miccoli, Paolo (European Journal of Pediatric Surgery, 2014)
Background Minimally invasive video-assisted thyroidectomy (MIVAT) proved to be safe and effective in the treatment of both benign and malignant disease. The aim of the present study is to compare MIVAT approach with conventional approach for total thyroidectomy in a group of 99 pediatric patients operated in the Department of General Surgery of the University of Pisa between March 2007 and July 2012.Patients A total of 99 pediatric patients under the age of 18 years with thyroid disease referred to our Department to undergo total thyroidectomy. Patients were divided into two groups according to the surgical technique performed: 34/99 (34.3%) patients (MIVAT group [MG]) and 65/99 (65.7%) patients, (conventional group [CG]) who underwent total thyroidectomy, respectively, with MIVAT approach and conventional approach.Results In MG mean operative time for total thyroidectomy was 40 ± 6.57 minutes (range 30–60 min); postoperative hospital stay was 1 day for 18 patients (53%), 2 days for 12 patients (35.25%), 3 days for 4 patients (11.8%); transient hypoparathyroidism (hypoPTH) was observed in 12 cases (35.3%) and permanent hypoPTH in 2 cases (5.9%); transient postoperative unilateral vocal cord palsy was observed in 2 patients (5.9%). In CG mean operative time for total thyroidectomy was 49.3 ± 12.9 minutes (range 30–80 min); postoperative hospital stay was 1 day for 16 patients (24.6%), 2 days for 40 patients (61.5%), 3 days for 8 patients (12.3%), and 4 days for 1 patient (1.6%); transient hypoPTH was observed in 23 cases (35.4%) and permanent hypoPTH in 4 cases (6.1%), who needed therapy with calcitriol and calcium carbonate; transient postoperative unilateral vocal cord palsy was observed in 4 patients (6.1%). There were no cases of permanent vocal cord paralysis in both groups. The correlation between two groups of patients showed that mean operative time was significantly lower in MG (p = 0.0007).Conclusion Pediatric patients of MG showed a significantly lower operative time and postoperative hospital stay with respect to pediatric patients of CG if compared with conventional technique. This result with the evidence of similar degree of completeness and rate of postoperative complications make MIVAT a valid option for the treatment of pediatric patients when performed by a well-trained staff in a third referral center.
Keywords: MIVAT; pediatric patients; conventional thyroidectomy